Energy flow in a household: A study on how to visualise and motivate energy saving behaviour - Lindström, Elin; Wieslander, Elin (My University, 2021)
Almost a third of the electricity in Sweden is used by households, and at approximately the same time of the day. This puts a strain on the electric grid and increases the risk of electricity shortage, mostly caused by lack of capacity. As the number of electric vehicles is increasing, the issue becomes even more pressing. There is therefore a need to enhance awareness among electricity consumers and their consumption behaviour. Furthermore, the installations of domestic solar power facilities has increased rapidly and is believed to continue to increase exponentially in the next few years. There is therefore also a need to support small-scale solar power producers and to integrate their production with their consumption. This master thesis has aimed to investigate how the flow of electricity throughout the household can be displayed, including both consumption, production via solar panels and charging of the electric vehicles. This thesis has also investigated what factors affect users’ energy consuming behaviour and how the consumption could be communicated so that they understand the environmental impact. The project was initiated with a market analysis to find similar solutions, followed by an explorative phase simultaneously as an ideation phase. During the exploration phase interviews with users and experts, questionnaires and literature studies were conducted. During the ideation phase, ideas to discuss and evaluate with users during the interviews were developed. These phases resulted in guidelines and insights that were used for the concept development. The concepts were prototyped and evaluated theoretically and with users with positive results. Lastly, a final design proposal was developed. The result is a design proposal integrating the household consumption, production and charge of the electric vehicles in the same mobile application. The application shows the flow of electricity in the household and information on production and consumption, and motivates and makes the user more aware of their consumption. Additionally, factors affecting the electricity consuming behaviour have been investigated and insights and guidelines for further development have been established.
Keywords: electricity, energy flow, mobile application, solar panels, electric vehicle, behaviour change, user studies